Deposition of SiOx Thin Films on Y-TZP by Reactive Magnetron Sputtering: Influence of Plasma Parameters on the Adhesion Properties Between Y-TZP and Resin Cement for Application in Dental Prosthesis - Calvacanti de Queiroz, Jose Renato [UNESP]; Duarte, Diego Alexandre; de Assuncao e Souza, Rodrigo Othavio; Fissmer, Sara Fernanda; Massi, Marcos; Bottino, Marco Antonio [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2011)
In this paper SiOx thin films were deposited on Y-TZP ceramics by reactive magnetron sputtering technique in order to improve the adhesion properties between Y-TZP and resin cement for applications in dental prosthesis. For fixed cathode voltage, target current, working pressure and target-to-substrate distance, SiOx thin films were deposited at different oxygen concentrations in the Ar+O-2 plasma forming gas. After deposition processes, SiOx thin films were characterized by profilometry, energy dispersive spectroscopy (EDS), optical microscopy and scanning electron microscopy (SEM). Adhesion properties between Y-TZP and resin cement were evaluated by shear testing. Results indicate that films deposited at 20%O-2 increased the bond strength to (32.8 +/- 5.4) MPa. This value has not been achieved by traditional methods.
Keywords: Y-TZP; dental material; thin films; silicon oxide